2020
DOI: 10.3389/fgene.2020.00279
|View full text |Cite
|
Sign up to set email alerts
|

A Chromosome-Scale Assembly of the Asian Honeybee Apis cerana Genome

Abstract: Apis cerana is one of the main honeybee species in artificial farming, which is widely distributed in Asian countries. The genome of A. cerana has been sequenced by several different research groups using second generation sequencing technologies. However, it is still necessary to obtain more complete and accurate genome sequences. Here we present a chromosome-scale assembly of the A. cerana genome using single-molecule real-time (SMRT) Pacific Biosciences sequencing and high-throughput chromatin conformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 30 publications
(37 reference statements)
3
28
0
Order By: Relevance
“…The assembled A. cerana genome contains 6.08% of repetitive sequences, and 0.7% of the genome are recognized as transposable elements (TEs). Mariner DNA transposons represent the most abundant TEs, consistent with previous reports for A. cerana in other countries [ 27 , 28 , 29 ].…”
Section: Resultssupporting
confidence: 90%
“…The assembled A. cerana genome contains 6.08% of repetitive sequences, and 0.7% of the genome are recognized as transposable elements (TEs). Mariner DNA transposons represent the most abundant TEs, consistent with previous reports for A. cerana in other countries [ 27 , 28 , 29 ].…”
Section: Resultssupporting
confidence: 90%
“…We examined the copy numbers for all transposons included in this study and found that most families of transposons had only one or few copies, which suggests that most Tc1/mariner and pogo transposons do not display significant amplification in these lineages. This is consistent with previous findings that most Tc1/mariner is detected with low genomic coverage [ 68 , 71 ]. In addition, we found >10 intact copies of DD34D/ mariner in the genomes of Apis mellifera , Apis mellifera carnica , Apis mellifera caucasia , Apis mellifera mellifera, and Euglossa dilemma .…”
Section: Discussionsupporting
confidence: 94%
“…DNA transposons are the major repeat sequence, and mariner transposons are the most common element within this class [ 70 ]. A recent study reported that TEs in the genome of the Asian honeybee Apis cerana accounted for 9.15% and simple repeats accounted for most TEs [ 71 ]. The DNA transposons constitute 0.11% (247 kb) of the Apis cerana genome and 0.57% (1.34 Mb) of the Apis mellifera genome.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we performed further analyses of Am genome data. While processing the present study, new and high-quality Acc genome data (Acc_new) were published (Wang et al 2020). To assess whether the results of RepeatMasker, particularly MLEs, were affected by the quality of input genome data, the detection of MLEs by RepeatMasker was conducted under the same conditions using Acc_new.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in the MLE numbers detected between these Apis species were not due to the reference genome qualities of the six Apis species. For example, new Acc genome data were published during the processing of the present study (Wang et al 2020), and we attempted to detect MLEs using these data under the same conditions as those for other Apis genomes. Although the contig N50 values of new Acc genome data were more than 150-fold higher than that of the Acc genome used in the present study (Table 1), the numbers of MLEs detected were not markedly different between the two sets of genome data.…”
Section: Discussionmentioning
confidence: 99%